Comparative Study of the Risk Factors for Musculoskeletal Disorders among Primary and Secondary School Teachers in the City of Cotonou (Benin) - ZOMALHETO, COSSI ZAVIER; MIKPONHOUE, ROSE; ADJOBIMEY, Mênonli (My University, 2019)
The objective is to compare the risk factors for MSDs among primary and secondary school teachers in Cotonou city. Cross sectional prospective study with a descriptive and analytical focus on 340 teachers: 170 in primary and 170 in secondary schools. Data collection was done using the standard Nordic MSDs questionnaire and a systematic physical examination. A logistic regression was done. Primary school teachers suffered more MSDs than secondary school teachers (80% vs. 69.4%, p=0.0025); scapulalgia (59.4% in primary school and 55.9% in secondary school) and neck pain (41.8% in primary school and 34.1% in secondary school) predominated in both categories. Factors associated with MSDs in both education subsectors were: seniority in employment (p=0.0006); stress (p=0.00135) and job dissatisfaction (p=0.0098). Job dissatisfaction and stress predominated among elementary school teachers (p<0.001). The prevalence of MSDs is higher among primary school teachers than among secondary school teachers. This may be related to the prevalence of psycho-social problems among primary school teachers. A revaluation of their working conditions is necessary to ensure their development at work and limit MSDs among them.
Keywords: Musculoskeletal disorders; Teachers